Integrated Metagenomic and Transcriptomic Analyses Reveal the Dietary Dependent Recovery of Host Metabolism From Antibiotic Exposure - Li, Bingbing; Qiu, Huihui; Zheng, Ningning; Wu, Gaosong; Gu, Yu; Zhong, Jing; Hong, Ying; Ma, Junli; Zhou, Wen; Sheng, Lili; Li, Houkai (Frontiers in Cell and Developmental Biology, 2021)
The balance of gut microbiome is essential for maintaining host metabolism homeostasis. Despite widespread antibiotic use, the potential long-term detrimental consequences of antibiotic for host health are getting more and more attention. However, it remains unclear whether diet affects the post-antibiotic recovery of gut microbiome and host metabolism. In this study, through metagenomic sequencing and hepatic transcriptome analysis, we investigated the divergent impacts of short-term vancomycin (Vac) or ciprofloxacin and metronidazole combination (CM) treatment on gut microbiome and host metabolism, as well as their recovery extent from antibiotic exposure on chow diet (CD) or high fat diet (HFD). Our results showed short-term Vac intervention affected insulin signaling, while CM induced more bacterial function changes. However, Vac-induced long-term changes of species were more apparent when recovered on CD than HFD. The effects of antibiotic intervention on host metabolism were long-lasting, antibiotic-specific, and diet-dependent. The number of differentially expressed gene was doubled by Vac than CM, but was comparable after recovery on CD as revealing by the hepatic transcriptomic analysis. In contrast, HFD intake during recovery could worsen the extent of post-antibiotic recovery by altering infection, immunity, and cancer related pathways in short-term Vac-exposed rats and by shifting endocrine system associated pathways in CM-exposed rats. Together, the presented data demonstrated the long-term recovery extent after different antibiotic exposure was diet-related, highlighting the importance of dietary management during post-antibiotic recovery.